2017
DOI: 10.1071/ah15189
|View full text |Cite
|
Sign up to set email alerts
|

Using a community of practice to evaluate falls prevention activity in a residential aged care organisation: a clinical audit

Abstract: Objective This study evaluates whether a community of practice (CoP) could conduct a falls prevention clinical audit and identify gaps in falls prevention practice requiring action. Methods Cross-sectional falls prevention clinical audits were conducted in 13 residential aged care (RAC) sites of a not-for-profit organisation providing care to a total of 779 residents. The audits were led by an operationalised CoP assisted by site clinical staff. A CoP is a group of people with a shared interest who get togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 22 publications
(22 reference statements)
0
25
0
Order By: Relevance
“…Technology development in the RAC sector is looking to provide low‐cost, asynchronous training options such as e‐learning accessed online, which will require staff to have computer literacy skills (Hanssen, Norheim, & Hanson, ). However, previous studies amongst nurses and allied health staff have identified that a technology usability gap exists (Francis‐Coad et al, ). Explanations for the usability gap may be linked to the age bracket of staff employed in RAC as predominantly 40–60 years meaning their exposure to technology is more limited (Hanssen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technology development in the RAC sector is looking to provide low‐cost, asynchronous training options such as e‐learning accessed online, which will require staff to have computer literacy skills (Hanssen, Norheim, & Hanson, ). However, previous studies amongst nurses and allied health staff have identified that a technology usability gap exists (Francis‐Coad et al, ). Explanations for the usability gap may be linked to the age bracket of staff employed in RAC as predominantly 40–60 years meaning their exposure to technology is more limited (Hanssen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study reports on one aspect of a large mixed methods fall prevention project conducted in an Australian RAC organisation (Francis‐Coad, Etherton‐Beer, Bulsara, Nobre, & Hill, ). Briefly, the project evaluated how a group of interdisciplinary RAC staff with a common interest in falls prevention (community of practice) identified gaps in fall prevention practice (Francis‐Coad, Etherton‐Beer, Bulsara, Nobre, & Hill, ), prioritised goals collaboratively and implemented selected falls prevention strategies across the RAC organisation (Francis‐Coad, Etherton‐Beer, Bulsara, Blackburn, Chivers, & Hill, ). One of the identified gaps in practice was the lack of evidence‐based falls prevention education provided for care staff and unknown understanding of their fall prevention knowledge and education preferences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During period three the CoP met via web-based discussion forums supported by face to face meetings to plan and conduct a falls prevention audit identifying gaps in practice. 20 In periods four, five and six the CoP developed and implemented falls prevention activities, where the CoP determined the timing and type of interventions that occurred (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A falls prevention CoP was established, piloted and then operationalized across the RAC organization. 20 The falls prevention CoP was considered an intervention at organization level as it acted across all 13 RAC sites. Findings from the pilot study facilitated CoP operationalization and activity across the sites.…”
Section: Interventionmentioning
confidence: 99%